Can a gradual weaning and separation process reduce weaning distress in dam-reared dairy calves? A comparison with the 2-step method - Vogt, Anina; Barth, Kerstin; Waiblinger, Susanne; König von Borstel, Uta; Justus Liebig University Giessen (My University, 2024)
The weaning and separation phase remains one of the biggest challenges for cow-calf contact systems, but a gradual process that better mimics the naturally occurring reduction in milk intake has not yet been scientifically investigated. Therefore, the aim of our study was to compare behavioral and physiological indicators of distress in 3-mo-old dam-reared dairy calves (with previous full-time cow-calf contact) weaned and separated either via gradual reduction of contact time with the dam (GR; 1 wk of half-day contact, 1 wk of morning contact, and 1 wk of fence-line contact before complete separation, n = 18) or via 2-step weaning using a nose flap (NF, 2 wk of access to the dam with a nose flap, 1 wk of fence-line contact before complete separation, n = 18). Behavior was recorded 1 wk before (or for lying 3 wk before) weaning start and during the 3 wk weaning and separation period with direct observations on 4 d/wk or via accelerometers (locomotor play, lying behavior). Blood and fecal samples were taken twice per week from weaning start until 3 wk after weaning start. Calves were weighed weekly. Statistical analysis was conducted using (generalized) linear mixed models. Over the whole weaning and separation phase, NF calves showed a stronger decrease in the number of lying bouts, amount of locomotor play, and ADG, as well as a higher increase in TMR feeding time compared with GR calves, whereas GR calves vocalized more often and showed more searching behavior than NF calves. Also, the neutrophil:lymphocyte ratio of NF calves was elevated on d 3 after insertion of the nose flaps compared with baseline, but showed no change for GR calves on any sampling day. Overall, results point toward a favorable effect of a gradual weaning strategy on reduction of weaning and separation distress in dam-reared dairy calves, but the method requires further improvement from the protocol used in our study.
Keywords: ddc:630